The efficacy of feed additives in alleviating heat stress and supporting gut health in poultry - Olayiwola, Sammad F.; Adedokun, Sunday A. (Frontiers in Animal Science, 2025)
Heat stress (HS) poses a critical challenge to modern poultry production, with increasing frequency and severity driven by global climate change. Heat stress impairs feed intake, nutrient absorption, growth, reproduction, immune competence, and welfare, resulting in substantial economic losses. The physiological consequences of HS include acid-base imbalance, endocrine and immune dysregulation, oxidative stress, altered gut integrity, and upregulation of heat shock proteins, which collectively compromise birds’ performance and survivability. Over the years, antibiotics have been incorporated into poultry feed as growth-promoting agents to enhance performance and efficiency; however, they are increasingly restricted due to concerns about antimicrobial resistance and residues in poultry products. To reduce antibiotic use, feed additives have emerged as promising nutritional strategies to mitigate HS-induced effects while serving as effective antibiotic alternatives. This review synthesizes current evidence on antibiotic growth promoters, mycotoxin binders, prebiotics, probiotics, synbiotics, postbiotics, exogenous enzymes, and phytochemicals, including essential oils, and their roles in enhancing thermotolerance, nutrient utilization, and overall health in heat-stressed poultry. These additives confer benefits by modulating gut microbiota, strengthening epithelial barriers, enhancing antioxidant and anti-inflammatory capacity, stabilizing immune and endocrine responses, and improving skeletal and eggshell integrity under high ambient temperatures. Dietary feed additives offer sustainable, non-antibiotic approaches to support poultry resilience, productivity, and welfare under the pressures of HS and the broader challenges of a warming climate. Future research should focus on mechanistic pathways, optimal dosing, and synergistic additive combinations tailored to species, age, and production systems to maximize thermotolerance and production efficiency.